2022
DOI: 10.3390/antiox11102006
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase MLL1 Mediates Oxidative Stress and Apoptosis upon Deoxynivalenol Exposure in the Intestinal Porcine Epithelial Cells

Abstract: Deoxynivalenol (DON), as a secondary metabolite of fungi, is continually detected in livestock feed and has a high risk to animals and humans. Moreover, pigs are very sensitive to DON. Recently, the role of histone modification has drawn people’s attention; however, few studies have elucidated how histone modification participates in the cytotoxicity or genotoxicity induced by mycotoxins. In this study, we used intestinal porcine epithelial cells (IPEC-J2 cells) as a model to DON exposure in vitro. Mixed linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Mycotoxin is tightly linked with the transcriptional processes involved in NR-mediated regulation . Increasing evidence have shown that NRs exert cardinal roles in regulating DON-induced OS and inflammatory genes through the recruitment of histone modifiers. , Apart from mediating inflammatory processes through the activation of IL-8 and the suppression of IL-4 in T-reg, , NR4A2 (encodes the NURR1 protein) also inhibits the transcription of the OS gene. , Sodium butyrate (NaBu) is a short-chain fatty acid that increases the average daily weight gain of piglets, provides energy for intestinal epithelium, plays an immunomodulatory role, and also regulates lipid metabolism in the liver and intestine . Notably, as a vital ligand of NR and a natural HDAC inhibitor, NaBu could alleviate DON-induced OS and inflammation. , Moreover, NaBu exerts anti-inflammatory effects by increasing the H3K9ac profiles at promoter regions of the pro-inflammatory genes and enhancing NR PPARA activation. Therefore, we hypothesize NaBu resists DON-induced OS and the inflammatory response through histone acetylation recruited by NR4A2 .…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxin is tightly linked with the transcriptional processes involved in NR-mediated regulation . Increasing evidence have shown that NRs exert cardinal roles in regulating DON-induced OS and inflammatory genes through the recruitment of histone modifiers. , Apart from mediating inflammatory processes through the activation of IL-8 and the suppression of IL-4 in T-reg, , NR4A2 (encodes the NURR1 protein) also inhibits the transcription of the OS gene. , Sodium butyrate (NaBu) is a short-chain fatty acid that increases the average daily weight gain of piglets, provides energy for intestinal epithelium, plays an immunomodulatory role, and also regulates lipid metabolism in the liver and intestine . Notably, as a vital ligand of NR and a natural HDAC inhibitor, NaBu could alleviate DON-induced OS and inflammation. , Moreover, NaBu exerts anti-inflammatory effects by increasing the H3K9ac profiles at promoter regions of the pro-inflammatory genes and enhancing NR PPARA activation. Therefore, we hypothesize NaBu resists DON-induced OS and the inflammatory response through histone acetylation recruited by NR4A2 .…”
Section: Introductionmentioning
confidence: 99%
“…The threat posed by mycotoxins, especially Deoxynivalenol (DON), is another area of concern. However, emerging research on histone modification in mycotoxin-induced cytotoxicity offers hope for potential interventions [ 7 ]. Polyphenols hold significant promise as feed additives for pigs; they may mitigate the oxidative stress and intestinal toxicity induced by DON [ 8 ].…”
mentioning
confidence: 99%